Drought a global assessment - Wilhite, Donald A (Ed) (London Routledge, 2000)
Drought provide the scientific and policy community with information in the form of new technologies and methodologies land also define a new paradigm for drought planning and management in 21st century.The overview chapters and care studies included in t
Keywords: Droughts